Interlayer excitons diffusion and transport in van der Waals heterostructures - Yingying Chen; Qiubao Lin; Haizhen Wang; Dehui Li (Materials Futures)
The assembly of monolayer transition metal dichalcogenides (TMDs) in van der Waals heterostructures yields the formation of spatially separated interlayer excitons (IXs) with large binding energies, long lifetimes, permanent dipole moments and valley-contrasting physics, providing a compelling platform for investigating and engineering spatiotemporal IX propagation with highly tunable dynamics. Further twisting the stacked TMD monolayers can create long-term periodic moiré patterns with spatially modified band structures and varying moiré potentials, featuring tailored traps that can induce strong correlations with density–dependent phase transitions to modulate the exciton transport. The rich exciton landscapes in TMD heterostructures, combined with advancements in valleytronics and twistronics, hold great promise for exploring exciton-integrated circuits base on manipulation of exciton diffusion and transport. In this Review, we provide a comprehensive overview of recent progress in understanding IXs and moiré excitons, with a specific focus on emerging exciton diffusion and transport in TMD heterostructures. We put emphasis on spatial manipulation of exciton flux through various methods, encompassing exciton density, dielectric environment, electric field and structure engineering, for precise control. This ability to manipulate exciton diffusion opens up new possibilities for interconverting optical communication and signal processing, paving the way for exciting applications in high-performance optoelectronics, such as excitonic devices, valleytronic transistors and photodetectors. We finally conclude this review by outlining perspectives and challenges in harnessing IX currents for next-generation optoelectronic applications.